Implementation of curriculum integration at Pondok Pesantren PPMI Assalaam Surakarta - Trisnojoyo Trisnojoyo; Giyoto Giyoto; Imam Mujahid (Inovasi Kurikulum, 2025)
The integration of the pesantren curriculum with the education curriculum is still less than optimal due to several factors, but not all boarding schools fail in curriculum integration. This study aims to describe the implementation of an integrated curriculum model at Pondok PPMI Assalaam which includes three main aspects, namely curriculum planning, implementation, and evaluation. This research uses a qualitative approach with interviews, observations, and documentation studies as data collection techniques. The data analysis technique uses the Miles and Huberman interactive model, namely through the process of data collection, data reduction, data display, and conclusion or verification. The results showed that the implementation of an integrated curriculum was able to optimize the learning process by accommodating the needs of students comprehensively. Integrated curriculum planning includes the formulation of vision and mission, organizational structure, determination of school programs, selection and organization of materials, organization of learning activities, and selection of learning tools, resources and facilities. A holistic approach to education is applied to create a learning environment conducive to the overall development of students in terms of academic, spiritual and character aspects. Regular evaluations contribute to improving the effectiveness of the curriculum.   Abstrak Integrasi kurikulum pesantren dengan kurikulum pendidikan masih kurang optimal yang disebabkan oleh beberapa faktor, namun tidak semua boarding school gagal dalam integrasi kurikulum tersebut. Penelitian ini bertujuan untuk mendeskripsikan penerapan model kurikulum yang terintegrasi di Pondok PPMI Assalaam yang mencakup tiga aspek utama yaitu perencanaan, pelaksanaan, dan evaluasi kurikulum. Penelitian ini menggunakan pendekatan kualitatif dengan wawancara, observasi, dan studi dokumentasi sebagai teknik pengumpulan data. Teknik analisis data menggunakan model interaktif Miles dan Huberman yaitu melalui proses data collection, data reduction, data display, dan conclusion atau verification. Hasil penelitian menunjukkan bahwa penerapan kurikulum terintegrasi mampu mengoptimalkan proses pembelajaran dengan mengakomodasi kebutuhan peserta didik secara komprehensif. Perencanaan kurikulum terintegrasi mencakup perumusan visi dan misi, struktur organisasi, penentuan program sekolah, pemilihan dan pengorganisasian materi, pengorganisasian kegiatan pembelajaran, serta pemilihan alat, sumber, dan sarana pembelajaran. Pendekatan holistik dalam pendidikan diterapkan guna menciptakan lingkungan belajar yang kondusif bagi perkembangan peserta didik secara menyeluruh, baik dari aspek akademik, spiritual, maupun karakter. Evaluasi dilakukan secara berkala berkontribusi dalam meningkatkan efektivitas kurikulum. Kata Kunci: evaluasi kurikulum; kurikulum terintegrasi; pendidikan holistik; perencanaan kurikulum